2018
DOI: 10.1007/s11195-018-9543-y
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activities as Risk Factors of Rotator Cuff Lesions: A Prospective Cohort Study

Abstract: The aim of this study was to analyze the occurrence of rotator cuff impingement due to reduction of subacromial space height during complex shoulder motion to determine safety of sexual activities. The hypothesis was that such activities could be deleterious if not performed with precaution. To use a patient-specific 3D measurement technique coupling medical imaging and optical motion capture to evaluate the safety of various sexual positions according to subacromial compression. Descriptive laboratory study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Lastly, there was one study that collected data on the kinematic demands on the rotator cuff, based on the height of the subacromial space (Lädermann et al, 2018 ). This study found that the subacromial space height was lower for the watering can (~ 6.10 mm) and basset hound (~ 6.20 mm) positions compared to the scorpion (~ 0.91 mm), missionary (~ 1.27 mm), or superman (~ 1.76 mm) positions (Lädermann et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lastly, there was one study that collected data on the kinematic demands on the rotator cuff, based on the height of the subacromial space (Lädermann et al, 2018 ). This study found that the subacromial space height was lower for the watering can (~ 6.10 mm) and basset hound (~ 6.20 mm) positions compared to the scorpion (~ 0.91 mm), missionary (~ 1.27 mm), or superman (~ 1.76 mm) positions (Lädermann et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a recent study concluded that intercourse positions such as the scorpion, missionary, or superman may cause rotator cuff degeneration because of friction on the undersurface of the acromion (Lädermann et al, 2018 ). This is due to the reduced or minimal subacromial space height (Lädermann et al, 2018 ). However, it is not only subacromial impingement that might lead to rotator cuff degeneration but also the scapular morphology (Moor et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations